Binary Opposition And Multiculturalism Shown In The Struggle Of Mataram Kingdom Power During Reign Of Amangkurat I - Akun, Akun; Ernawati, Endang (Bina Nusantara University, 2012)
This research aims to learn a potential and a struggle of the Chinese in clash of power during Amangkurat I (1646-1677) reign. The Chinese role was represented by Rara Oyi and her parents, Ki and Nyi Mangun. Literature study is done by applying binary opposition which is part of Post Collonialism theory. Analysis is done by showing evidences related to Binary opposition, which are good versus bad, man versus woman, powerful versus powerless, majority versus minority, oppressor and oppressed, rich versus poor, and love versus hate. It can be concluded that all aspects of binary oppositios and multiculturalism are presented clearly in Rembulan Ungu novel written by Bondan Nusantara.